Innovative approach in Islamic elementary education: Effective strategies for enhancing education quality - Mariska, Refi; Mustakim, Zaenal (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
Effective learning in Islamic elementary schools necessitates the selection of approaches appropriate to specific learning models. This article aims to identify effective strategies, evaluate the impact of innovative approaches, and address particular challenges in this context. The research method involved an extensive literature review and analysis, utilizing descriptive data analysis to gain a comprehensive understanding of the collected data. This process included frequency counting, pattern identification, and data classification to discern trends, patterns, and key aspects. Teacher-centered approaches are typically associated with explanatory learning models, where the instructor plays a central role in delivering knowledge. Conversely, student-centered approaches align with constructivist learning models, emphasizing active student engagement and self-directed learning. Collaborative learning approaches support collaborative learning models, encouraging group work and peer-to-peer interaction, while project-based learning approaches are often linked to problem-based learning models, focusing on real-world problem-solving and critical thinking skills. Understanding these relationships is crucial for designing meaningful and effective learning experiences for students. By considering various learning approaches and models, instructors can select and implement the methods that best meet their students' diverse needs and learning objectives. Furthermore, integrating different learning approaches and models enhances student interaction, fosters deeper understanding, and promotes a more dynamic and engaging learning environment. Therefore, this article emphasizes the importance of effectively combining learning approaches and models to achieve the desired educational outcomes in Islamic elementary schools. By doing so, educators can create a more holistic and adaptable educational experience, ultimately leading to improved student performance and a deeper appreciation for lifelong learning.